2018
DOI: 10.1051/0004-6361/201731909
|View full text |Cite
|
Sign up to set email alerts
|

Detailed abundance analysis of globular clusters in the Local Group

Abstract: Context. Globular clusters (GCs) are emerging as powerful tracers of the chemical composition of extragalactic stellar populations. Aims. We present new abundance measurements for eleven GCs in the Local Group galaxies NGC 147, NGC 6822, and Messier 33. These are combined with previously published observations of four GCs in the Fornax and WLM galaxies. Methods. The abundances were determined from analysis of integrated-light spectra, obtained with the HIRES spectrograph on the Keck I telescope and with UVES o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
31
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 131 publications
(225 reference statements)
9
31
2
Order By: Relevance
“…The data from Galactic and extragalactic globular clusters (Larsen et al 2017(Larsen et al , 2018 also follow the [Mn/Fe] trends seen in data of field stars. This is interesting because globular clusters probe different star formation environments and ex-situ origin has been proposed for a substantial fraction, namely one quarter, of the Galactic GC systems (Pritzl et al 2005;Forbes & Bridges 2010).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The data from Galactic and extragalactic globular clusters (Larsen et al 2017(Larsen et al , 2018 also follow the [Mn/Fe] trends seen in data of field stars. This is interesting because globular clusters probe different star formation environments and ex-situ origin has been proposed for a substantial fraction, namely one quarter, of the Galactic GC systems (Pritzl et al 2005;Forbes & Bridges 2010).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, we include [Mn/Fe] abundances for seven Galactic globular clusters, obtained from integrated-light observations with UVES at VLT (Larsen et al 2017) and 15 extragalactic GCs observed with UVES and with HIRES on the A38, page 2 of 7 Keck I telescope (Larsen et al 2018). These abundance measurements were made by fitting custom-computed simple stellar population models to the integrated-light spectra, adjusting the input abundances in the models until the best fits to the data were obtained.…”
Section: Additional Datasetsmentioning
confidence: 99%
“…Interestingly, these clusters both have approximately Solar-scaled α-element abundances, in agreement with the trends seen in field stars in dwarf galaxies [25]. Cluster SC7 also exhibits a number of other peculiarities, including a significantly sub-Solar [Sc/Fe] ratio and low [Ni/Fe] and [Na/Fe] ratios [26]-indeed, its detailed chemical abundance patterns closely match those in the galactic GC Ruprecht 106, for which an accretion origin has been suggested [27]. A few GCs in the M31 with similar abundance patterns may likewise be accreted [23,24].…”
Section: Chemical Abundances Of Gcs In Dwarf Galaxiessupporting
confidence: 71%
“…Previous work (Suda et al 2017) discussed many aspects of stellar archaeology such as chemical evolution, astrometry, nucleosynthesis in stars, and comparison with the stars in the Galactic globular clusters. Abundance data can be applied to other events and phenomena; chemodynamical evolution of galaxies (Hirai et al 2018), comparisons with stellar yields from rotating first stars (Takahashi et al 2018), abundances in globular clusters in the local group (Larsen et al 2018) comparisons with the simulations of Λ CDM universe (Yves & Pascale), and so on.…”
Section: Final Remarksmentioning
confidence: 99%